Vehicle-Related Expressions in Turkish Cypriot Dialect - Pehlivan, Ahmet; Osam, Necdet (Ahmet Yesevi Univ, 2010)
Turkish Cypriot dialect (henceforth TCD), being one of the Anatolian dialects, is nowadays different with respect to vocabulary, from both Anatolian dialects and Turkish. This difference is due to its borrowed vocabulary stock, the frequent use of non-standard sentence structure, intonation pattern and so on. The primary reasons causing the difference can be cited as: (I) the isolation of the TCD from Anatolian dialects for a signif cant period, (II) the multicultural and multilingual context of the island. In this study, a detailed analysis of the vocational language (mechanics) will be carried out with specific reference to car, car parts and engine parts. Today when the language of mechanics is analyzed, it can be clearly noted that borrowed words constitute their language significantly. In addition to this, various words were derived from Turkish and new meanings were given to words in Turkish and Anatolian dialects. Finally there will be an opportunity to reflect the fact that a new type of vocabulary is generated with a different meaning from that of the Turkish and Anatolian dialects.
Keywords: Turkish Cypriot Dialect; Cypriot Turkish; mechanics' language; jargon; loanwords